1998
DOI: 10.1515/cclm.1998.145
|View full text |Cite
|
Sign up to set email alerts
|

Expert Systems for the Interpretation of Serum Proteins

Abstract: The ready availability of inexpensive desk-top computers with enormous disk storage has made the practicality of computer assisted medical interpretive software a reality. There seems little question that these programs could be of enormous help to physicians. However, there are daunting problems to their creation, including the lack of standards for clinical diagnostic precision or accuracy and paucity of helpful literature. As a result, the final products may be quite different. Little effort has been devote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…OS curves were estimated by the Kaplan-Meier method and compared using a log rank test. The lower normal limit of 18 mg/dL TTR 7 was used as a threshold to stratify patients. Survival time was measured from date of positive biopsy (diagnosis) to death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OS curves were estimated by the Kaplan-Meier method and compared using a log rank test. The lower normal limit of 18 mg/dL TTR 7 was used as a threshold to stratify patients. Survival time was measured from date of positive biopsy (diagnosis) to death.…”
Section: Methodsmentioning
confidence: 99%
“…14 Formerly known as prealbumin, TTR is a liver-secreted plasma protein that functions as a minor carrier of thyroxine and binding partner to retinol-binding protein 4 (RBP4). 5,6 Serum concentrations, normally 18–45 mg/dL, 7 are dependent on age, sex, race and nutritional status; moreover, TTR levels can fluctuate as a consequence of infection or generalized inflammatory states. 810 Several studies have shown significantly decreased TTR concentrations in inherited forms of TTR amyloidosis (ATTRm) and lower-range normal levels in a single small ATTRwt series.…”
Section: Introductionmentioning
confidence: 99%